2006
DOI: 10.1016/j.jacc.2006.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging and Transesophageal Echocardiography in Patients With Transcatheter Closure of Patent Foramen Ovale

Abstract: The present CMRI technique is inferior to TEE in detection of contrast-enhanced right-to-left shunting and identification of ASA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…In CaMRISS, 4 of these patients had a LGE of ≥3 dysfunctional wall segments (Table 4), indicating an independent risk factor for thrombus formation as shown in a previous study. 13 In accordance with previous publications, including either 25 21 or 75 patients with cryptogenic stroke, 22 respectively, contrast-enhanced cvMRI failed to properly assess left atrial shunts in CaMRISS patients. Despite of the fact that a patent foramen ovale-even in combination with an atrial septum aneurysm-or an atrial septum defect is considered to be a low or uncertain risk source of embolism, 24 this is a limitation of cvMRI in practice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In CaMRISS, 4 of these patients had a LGE of ≥3 dysfunctional wall segments (Table 4), indicating an independent risk factor for thrombus formation as shown in a previous study. 13 In accordance with previous publications, including either 25 21 or 75 patients with cryptogenic stroke, 22 respectively, contrast-enhanced cvMRI failed to properly assess left atrial shunts in CaMRISS patients. Despite of the fact that a patent foramen ovale-even in combination with an atrial septum aneurysm-or an atrial septum defect is considered to be a low or uncertain risk source of embolism, 24 this is a limitation of cvMRI in practice.…”
Section: Discussionsupporting
confidence: 82%
“…16,17 Moreover, cardiac MRI is superior to echocardiography on detection of recent or previous myocardial infarction. 18,19 Although a few MRI studies reported the prevalence of specific (potential) embolic sources after stroke, 15,[20][21][22] these studies did not provide a comprehensive statement on the diagnostic value of cardiovascular MRI (cvMRI) compared with the current gold standard of TEE and TTE assessment of acute ischemic stroke etiology.…”
Section: May 2017mentioning
confidence: 99%
“…5,10 -14 Although we have shown that present CMRI technique is inferior to TEE in detection of contrast-enhanced right-to-left shunting and identification of atrial septal aneurysm, 5 we could also demonstrate that routine CMRI after transcatheter closure of PFO is feasible and safe. 5,15,16 Velocity mapping CMRI is a well-validated approach to directly quantify the severity of regurgitant semilunar valves. [17][18][19][20][21][22] In combination with ventricular volumetric data, insufficiencies of the atrioventricular valves can be quantified with excellent reproducibility.…”
Section: Editorial See P 2967 Clinical Perspective On P 3008mentioning
confidence: 85%
“…Indication for PFO closure was based on cryptogenic ischemic events as defined elsewhere 5 and evidence of a PFO with contrast-enhanced interatrial right-to-left-shunt at rest or during Valsalva provocation as seen in transesophageal echocardiography. Diagnostic work-up before PFO closure included 12-lead ECG, Holter monitoring, Doppler sonography, transthoracic echocardiography, TEE, and coagulation blood tests.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation